NEW PHYTOSEIIDAE (ACARI: MESOSTIGMATA) FROM COSTA RICA, WITH ADDITIONAL INFORMATION on OTHER SPECIES - de Castro, Tatiane M. M. G. [UNESP]; de Moraes, Gilberto J.; McMurtry, James A. (Taylor & Francis Inc, 2010)
This paper reports on a study of phytoseiids collected from the La Selva Biological Field Station, the ALAS (Arthropods of La Selva) Project, made available to us by the Canadian National Collection via Dr. E. E. Lindquist. This material includes two new species, Proprioseiopsis versus n. sp. and Transeius costarricensis n. sp., three new records for Central America, and additional information for nine species previously reported from La Selva.
Keywords: Taxonomy; predatory mite; Biological control; La Selva; Central America